Maternal cortisol slope at 6 months predicts infant cortisol slope and EEG power at 12 months - St. John, Ashley M. (Dev Psychobiol, 2017)
Physiological stress systems and the brain rapidly develop through infancy. While the roles of caregiving and environmental factors have been studied, implications of maternal physiological stress are unclear. We assessed maternal and infant diurnal cortisol when infants were 6 and 12 months. We measured 12-month infant electroencephalography (EEG) 6–9 Hz power during a social interaction. Steeper 6-month maternal slope predicted steeper 12-month infant slope controlling for 6-month infant slope and breastfeeding. Steeper 6-month maternal slope predicted lower 6–9 Hz power. Six-month maternal area under the cuve (AUCg) was unrelated to 12-month infant AUCg and 6–9 Hz power. Psychosocial, caregiving, and breastfeeding variables did not explain results. At 6 months, maternal and infant slopes correlated, as did maternal and infant AUCg. Twelve-month maternal and infant cortisol were unrelated. Results indicate maternal slope is an informative predictor of infant physiology and suggest the importance of maternal physiological stress in this developmental period.